Recent advances and role of melatonin in post-harvest quality preservation of shiitake (Lentinula edodes) - Asdullah, Hafiz Umair; Chen, Feng; Hassan, Muhammad A.; Abbas, Asad; Sajad, Shoukat; Rafiq, Muhammad; Raza, Muhammad Adnan; Tahir, Arslan; Wang, Dongliang; Chen, Yougen (Frontiers in Nutrition, 2024)
Shiitake mushrooms are renowned for their popularity and robust nutritional value, are susceptible to spoilage due to their inherent biodegradability. Nevertheless, because of their lack of protection, these mushrooms have a short shelf life. Throughout the post-harvest phase, mushrooms experience a persistent decline in quality. This is evidenced by changes such as discoloration, reduced moisture content, texture changes, an increase in microbial count, and the depletion of nutrients and flavor. Ensuring postharvest quality preservation and prolonging mushroom shelf life necessitates the utilization of post-harvest preservation techniques, including physical, chemical, and thermal processes. This review provides a comprehensive overview of the deterioration processes affecting mushroom quality, covering elements such as moisture loss, discoloration, texture alterations, increased microbial count, and the depletion of nutrients and flavor. It also explores the key factors influencing these processes, such as temperature, relative humidity, water activity, and respiration rate. Furthermore, the review delves into recent progress in preserving mushrooms through techniques such as drying, cooling, packaging, irradiation, washing, and coating.